Parameter estimation of cocomo model using the jaya algorithm for software cost estimation - Tan, Jie Chee (2019)
In line with the advancement of computer technology, software is increasingly being used in place of hardware to help human do the daily chores. Estimate of the software development costs can be a major issue (i.e. in terms of determining the actual development costs). To date, many techniques have been proposed to help the software engineer determine the actual software cost. This thesis proposed the Jaya algorithm based on estimation of the software based on the COCOMO I model. The Constructive Cost Model (COCOMO) is a procedural software cost estimation model developed by Barry W. Boehm. In this case, the estimation of value of the COCOMO model parameters are determined for the cost and time estimation of the COCOMO model. As a result, COCOMO Jaya Algorithm (COCOMO JA) has been developed. The dataset NASA 63 project, Turkish dataset, and Kemerer dataset have been used. The experiment result shows the comparison between the standard COCOMO and COCOMO JA. The COCOMO JA demonstrated more minimize error as compare to the standard COCOMO. In conclusion, the JA suitable to evaluate the estimation effort and time for the COCOMO model.